Mutational pattern in Capsid Protein (C) of Dengue Virus isolates from Punjab Province of Pakistan - Saira Musshtaq; Muhammad Tahir Khan; Malik Ihsan Ullah Khan; Maira Mahmood; Farhat Humayun; Aneeqa Shahid (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Dengue virus (DENV) genomic study is crucial for understanding how it spreads and presents and become dangerous. Three structural and seven non-structural proteins are encoded by the positive stranded RNA DENV. Capsid protein (C) is one of the structural proteins which helps in the encapsidation of viral RNA. Objective of the study is to identify the DENV serotypes and the most common geographic specific mutations in the C protein, circulating in Punjab province of Pakistan.METHODOLOGY: It was cross sectional study in which About 120 DENV isolates were selected, by the procedure of temporal sampling done in peak season of dengue fever in 2022, from the major tertiary care hospitals for whole genomes sequence analysis. Among which only 23 whole genomes sequences were performed after virus isolation, quantification and cDNA synthesis.RESULTS: All the samples were found to be of genotype 1 and 2 in which 44 non-synonymous mutations were detected in the C protein. The most common mutations were; N90S (n=11) and G70S (n=11) followed by V26G (n=5) and R10Q (n=4), in which G70S is novel.CONCLUSION: Mutations in the current study are of particular interest to design of DENV vaccine projects in future. Genomic epidemiology during each outbreak of DENV in different locations is critical for better public health and for designing new policies for future outbreaks.